Prevalence of metronidazole resistant Helicobacter pylori strains among Chinese peptic ulcer disease patients and normal controls in Hong Kong. Issue 5 (May 1996) - Ching, C K; Leung, K P; Yung, R W; Lam, S K; Wong, B C; Lai, K C; Lai, C L
Abstract : BACKGROUND--A study was conducted to evaluate the prevalence of metronidazole resistant Helicobacter pylori strains among the Chinese in Hong Kong. The efficacy of the triple therapy that contains metronidazole as one of the anti-microbial agents in eradication of the metronidazole susceptible and the metronidazole resistant strains was also assessed. METHODS--Culture for H pylori was attempted from antral biopsy specimens of 70 peptic ulcer and 51 control subjects. Successfully cultured H pylori strains were tested for metronidazole susceptibility. Twenty six peptic ulcer disease subjects who had received a course of triple therapy were also reassessed four to six weeks later for successful eradication of H pylori infection. RESULTS AND CONCLUSIONS--H pylori was successfully cultured from antral biopsy specimens in 69 of 80 (86%) of the infected subjects. The overall metronidazole resistance rate was 53.5% (37 of 69). There was a significantly higher metronidazole resistance rate among H pylori isolates from the asymptomatic controls (20 of 25) than the peptic ulcer disease subjects (17 of 44) (p = 0.0007). Twenty three of 32 (73%) women and 14 of 37 (38%) men harboured the metronidazole resistant strains. There was no sex or age difference as far as the prevalence of metronidazole resistant strains were concerned within each study group. Pre-treatment metronidazole susceptible H pylori were significantly more likely to respond to the triple therapy used than those with the metronidazole resistant ones (14 of 15 v five of 10) (p = 0.021).